2007
DOI: 10.1291/hypres.30.643
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Categories and Cardiovascular Risk Factors in Japan: The Jichi Medical School (JMS) Cohort Study

Abstract: Few studies have reported on risk factors by blood pressure categories based on antihypertensive treatment in the general population. We examined the associations between blood pressure categories and other risk factors in Japan. Cross-sectional study, multicenter population-based study was designed. A total of 11,302 men and women were eligible. Data were obtained from April 1992 to July 1995 in 12 rural districts in Japan. Subjects were divided into three categories: normotensives (with blood pressure <140/9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This study showed that 79.2% of the subjects had two or more preexisting risk factors and only two subjects had no risk factor. This proportion was similar to the results of the previous studies which evaluated the number of risk factors of MI among patients without MetS (28)(29)(30). These findings suggest that a long duration of multiple risks may cause CHD in Japanese.…”
Section: Discussionsupporting
confidence: 89%
“…This study showed that 79.2% of the subjects had two or more preexisting risk factors and only two subjects had no risk factor. This proportion was similar to the results of the previous studies which evaluated the number of risk factors of MI among patients without MetS (28)(29)(30). These findings suggest that a long duration of multiple risks may cause CHD in Japanese.…”
Section: Discussionsupporting
confidence: 89%
“…1820 In this article we utilize data from the JMS Cohort Study to develop risk assessment charts for MI.…”
Section: Introductionmentioning
confidence: 99%
“…, Takayuki MASAKI 2) , Eri ONO 1) , Takeshi ETO 1) , Tetsu IWAO 1) , Nobuoki ESHIMA 3) , Tetsunori SAIKAWA 4) , and Hironobu YOSHIMATSU 2) Introduction Hypertension has been recognized as a major risk factor for several cardiovascular diseases (1)(2)(3). In its seventh report, the 2003 Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC-7) defined a new set of guidelines for the prevention and management of hypertension.…”
mentioning
confidence: 99%